A New Window on Interaction: Does Mindfulness Play a Role? - Khonamri, Fatemeh; Soleimani, Mahsa; Gadušová, Zdenka; Pavera, Libor (Journal of Education Culture and Society, 2022)
Aim. The paper aims to investigate the students interactions engaged in mindful tasks in an English reading classroom. It attempts to explore whether there is any connection between being mindful and having a good interaction. Methods. For the research a case study approach was utilised, in which eight BA students majoring in English language and literature at the University of Mazandaran participated. They were divided into two groups of non-mindful and less mindful, each having four members based on their scores from Mindful Attention Awareness Scale (MAAS). The data was collected in three sessions of critical reading practice, in which both groups were engaged in different forms of critical reading tasks. The less mindful group was encouraged to engage in some mindful activities prior to the critical reading tasks. All the sessions were video recorded and then transcribed for analysis. The transcribed data were analysed by the researcher and a second rater. Results. The results of the data analysis demonstrated that there were some minor differences in interactions of non-mindful and less-mindful group in critical reading tasks. The less-mindful group seemed to have more interactions than the non-mindful one. Conclusions. Due to the study limitations the results cannot be generalised. Originality. Mindfulness is a fairly new concept in English language teaching which is attracting attention as an alternative to promote learning. However, within the context of education, there have also been a select few studies that have focused on the benefits of mindfulness in English reading classrooms.